Neighbourhood SME financing: Tunisia - Sarah Stölting (European Investment Bank (EIB), 2015)
This study was undertaken by the EIB Economics Department. The study assesses the financing needs of the SMEs in the Neighbourhood countries that have signed Deep and Comprehensive Free Trade Area agreements with the EU. In particular the study addresses the needs of the intermediaries that specialize in SME financing and examines the potential for different types of financial products including equity, guarantees, trade finance and other risk-bearing instrument.
Keywords: 330; Unternehmensfinanzierung; KMU; Tunesien